International Human Rights Law as a Mechanism for Coping with Climate Change - Cüneyt Yüksel (Ceza Hukuku ve Kriminoloji Dergisi)
The negative impacts of climate change emerge more intensely with each day. Moreover, the fear is that these negative effects will further increase if the current situation continues as is. The risks brought about by global climate change will obviously have important consequences on human rights. In this context, climate change and the measures that are or will be taken for coping with this threat are seen to have been evaluated within a human rights-oriented approach, especially in recent years. Indeed, the effective use of mechanisms established by international law for the purpose of protecting human rights can be anticipated to play an important role in minimizing the negative impacts of climate change. However, the unique nature of the relationship between climate change and human rights brings with it some debates that need to be resolved. This article concerns itself with the approach adopted in this new challenge encountered by international law through an analysis of the developments observed through the jurisprudence of the European Court of Human Rights, the policy-making processes of the Parliamentary Assembly of the Council of Europe, the Committee of Ministers of the Council of Europe, and the United Nations.